WHAT'S IN THE TEXTBOOK AND WHAT'S IN THE MIND: Polarity Item "Any" in Learner English. Issue 1 (9th May 2017) - Marsden, Heather; Whong, Melinda; Gil, Kook-Hee
Abstract: This paper presents an experimental study of the rarely explored question of how input through instruction interacts with L2 acquisition at the level of modular linguistic knowledge. The investigation focuses on L2 knowledge of the English polarity item any, whose properties are only partially covered by typical language-teaching materials. We investigate Najdi-Saudi Arabic-speaking learners' knowledge of the distribution of any in contexts that are taught, contexts that are not taught but may be observable in the input, and contexts that are neither taught nor observable. We further test whether conscious awareness of instructed rules about any correlates with performance. Our findings suggest a role for instruction and for internal, UG-constrained acquisition, and that these two paths interact. We explore our findings in terms of Sharwood Smith and Truscott's (2014a, 2014b ) framework of modular online growth and use of language, in which cognitive development is driven by processing.